Review on Halal Cluster - Puspita, Amelia Tri; Rahardjo, Sri; Rahayu, Solihah Sari (SMART Insight, 2023)
The increasing awareness of the Muslim community in Indonesia towards the halalness of every product eaten causes an increasing demand for halal food. The development of the halal industry must be supported by the development of the right halal supply chain. Halal supply chain as a process of managing halal food products from various supplier points to various consumer points, involving various parties, located in different places, which may be at the same time, involved with managing halal food products, with the aim of meeting the needs and requirements of customers. To ensure the availability and access of halal food, a new paradigm is needed in better structuring halal food production and trade through halal clusters. This study aims to determine the development map and trend of the Halal Cluster published by reputable journals in the field of Halal Economics. The data analyzed were 30 Dimensions indexed research publications. The export data is then processed and analyzed using the R Biblioshiny application program to find out the bibliometric map of the development of the Halal Cluster. This research will also analyze thematic maps that appear based on density and centrality which are analyzed based on document titles with the research theme of Halal Cluster which is divided into 4 quadrants. These results are obtained from a semi-automatic algorithm by reviewing the titles of all references to the object of research